ChemInform Abstract: Armillariols A to C from the Culture broth of Armillaria sp. Issue 4 (28th January 2014) - Kobori, Hajime; Sekiya, Atsushi; Yasuda, Nobuhiro; Noguchi, Keiichi; Suzuki, Tomohiro; Choi, Jae‐Hoon; Hirai, Hirofumi; Kawagishi, Hirokazu
Abstract Three novel lettuce hypocotyl and root growth regulating compounds, armillariols A (I), B (II), and C (III), are isolated from the culture broth of Armillaria sp.